Creatine supplementation and maximal rate of lactate accumulation following a 15-second all-out sprint test - Meixner, B.; Nusser, V.; Koehler, K.; Sperlich, B. (Journal of Science and Cycling, 2024)
vLamax is traditionally tested in a 15-s all-out sprint test. The variable is based on Mader`s model of energy system contributions and acts as a surrogate for the maximal glycolytic rate. On this foundation, vLamax is not only used as a predictor for sprint performance but for endurance efforts as well. The aim of this study was to determine the effect of creatine supplementation on the results of testing procedure. 12 amateur cyclists (more forthcoming) were recruited. Participants performed a 15-s all-out sprint test on a Cyclus2-ergometer. Capillary blood lactate was sampled in the 8 minutes following the test. Participants underwent the testing procedure four times under different conditions in this order: a familiarization trial, baseline, placebo (4x5 g/d maltodextrin for 5 d) and creatine supplementation (4x5 g/d creatine monohydrate for 5 d). Weight and body composition was determined using BIA on each visit. At present state, ANOVA revealed significant a significant increase in fat-free mass under the creatine condition compared to all other conditions. For all other measures (peak and mean power output, ?La, calculated total body lactate production), no differences were found between different conditions. Based on the data at hand, a loading phase of creatine supplementation increases fat-free mass. Tendencies of mean values across groups show an increase in mean power output over the 15-s all-out sprint test under the creatine condition while simultaneously decreasing DLa compared to baseline and placebo condition. However, no statistical significance was reached. Further research is needed to determine the influence of a popular ergogenic aid on metabolic testing of glycolytic rate.